Teaching Process and Subjects in National Schools of Turkestan During the Colonial Period - Ochilova, Gulmira (International Journal on Integrated Education, 2023)
In the late 19th and early 20th centuries, Turkestan had its own education system. The national education system was in crisis when the founders of the colonial system began to destroy the educational system that had developed over a long historical period. By the 1920s, schooling, which included national schools, riding schools, karkhana, dalailkhana and madrasas, was treated as a "place of superstition". The general state of national schools in the early 20th century was repeatedly criticised by modernists in the press. However, it is appropriate to give information about the educational process, form of teaching and subjects of study in the schools of Turkestan at this time.